Perancangangan Desain Board Game Penjumlahan dan Pengurangan sebagai Alat Bantu Pembelajaran Matematika Guru Sekolah Dasar Kelas 1 dan 2 - Rahmawati, Ermiana; Arifianto, Pungky Febi; Daniar, Aninditya (Innovative: Journal Of Social Science Research, 2024)
This design is used to design an addition and subtraction board game as a learning aid for grade 1 and 2 students in mathematics that can be used by elementary school teachers. Designing board game designs in research is useful so that students do not undergo monotonous learning so that learning becomes less enjoyable. This design method is used to obtain data that produces concepts that can be used in designing board games. This data was obtained from interviews with psychologists and pediatricians, FGD (Focus Group Discussion) with students, and a survey of 11 elementary school teachers.